Efficient radiative cooling coating with biomimetic human skin wrinkle structure. (November 2021) - Cheng, Ziming; Han, Han; Wang, Fuqiang; Yan, Yuying; Shi, Xuhang; Liang, Huaxu; Zhang, Xinping; Shuai, Yong
Abstract: Daytime radiative cooling is an energy-free pathway to achieve cooling performance. Current radiative cooling materials with periodic photonic structures are facing a huge challenge in terms of scale expansion owing to complex preparation technology and high cost. Herein, we proposed the idea of using biomimetic wrinkle structure combined with optimized particles to achieve the efficient optical property regulation of both the solar band and "atmospheric window" band. On this basis, a large-scale radiative cooling coating with the biomimetic structure of human skin natural wrinkle, comprising high concentrations of BaSO4 and SiO2 particles, was demonstrated. The coating with a thickness of ~100 µm reflected ~95% of solar irradiance, and the emissivity in the "atmospheric window" band was ~96%. At noontime (11:00–13:00), in a populous area located at sea level, the average effective cooling power of ~89.6 W/m 2 was recorded, and the maximum sub-ambient temperature drop can reach 8.1 °C. An outdoor-building test conducted over a year showed that the maximum average indoor air temperature of the building painted with the coating was reduced by 6.2 °C and the maximum power-saving rate of air-conditioning exceeded 50%. Our work provided a new idea for designing, fabrication, and application of high-performance radiative cooling materials. Graphical Abstract: Inspired by the human skin wrinkle structure, the Bio-RC coating was designed, prepared, characterized and tested at outdoor actual buildings. ga1 Highlights: ● Idea of using biomimetic wrinkle structure to control optical property was proposed. ● The Bio-RC coating with biomimetic structure of human skin wrinkle was fabricated. ● The R ¯ solar  = ~95% and ε ¯ atm  = ~96% of Bio-RC coating were higher than that of planar coating. ● Achieved sub-ambient cooling of ~8.1 °C and average cooling power of ~89.6 W/m 2 . ● A year-round test of Bio-RC coating painted on an outdoor building was conducted.